2012
DOI: 10.1158/1078-0432.ccr-11-2019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genomics on Personalized Cancer Medicine

Abstract: Recent advances in tumor genetics and drug development have led to the generation of a wealth of anticancer targeted therapies. A few recent examples indicate that these drugs are mainly, if not exclusively, active against tumors of a particular genotype that can be identified by a diagnostic test, usually by detecting a somatic alteration in the tumor DNA. However, for the majority of targeted therapies in development, there are still no clinical tools to determine which patients are most likely to benefit or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 51 publications
0
53
0
Order By: Relevance
“…The treatment of many solid tumors has shifted toward a "personalized approach" where tumor-specifi c molecular abnormalities are targeted with appropriately matched pharmacologic inhibitors ( 5 ). However, to identify clinically relevant molecular targets, one must use appropriate profi ling techniques.…”
Section: B R C a 2 B R A F T P 5 3 S M A D 4 C D K N 2 A C D K N 2 B mentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of many solid tumors has shifted toward a "personalized approach" where tumor-specifi c molecular abnormalities are targeted with appropriately matched pharmacologic inhibitors ( 5 ). However, to identify clinically relevant molecular targets, one must use appropriate profi ling techniques.…”
Section: B R C a 2 B R A F T P 5 3 S M A D 4 C D K N 2 A C D K N 2 B mentioning
confidence: 99%
“…Median overall survival (14-38 months) is improved with surgical resection, but few patients achieve durable responses from chemotherapy and/or radiotherapy ( 1 , 4 ). Unlike other solid tumors in which targeted therapies against matched molecular aberrations have proven superior to chemotherapy ( 5 ), few such targets have been identifi ed in PACC. Studies investigating the genomics of PACC have observed activation of the β-catenin pathway, broad chromosomal gains and losses encompassing multiple genes, and somatic inactivation of tumor-suppressor genes (e.g., SMAD4 , RB1 , BRCA2 , and TP53 ; refs.…”
Section: Introductionmentioning
confidence: 99%
“…While it is known that the functional inactivation of pRB causes major changes, beyond the fact that these cells are more easily driven into the cell cycle, we currently understand very little about the range of cellular processes that are altered when pRB is lost. A major initiative in cancer research is the idea of personalized medicine and the use of treatments that are tailored to the unique properties of each tumor (Haber et al 2011;Arteaga and Baselga 2012). This concept relies on the idea that changes in specific oncogenes/tumor suppressor genes generate unique dependencies that can be exploited.…”
mentioning
confidence: 99%
“…Indeed, other investigators have shown that specific molecular testing for these aberrations and use of agents to target these aberrations is associated with improved clinical outcomes (8,10,(28)(29)(30)(31)(32)(33)(34). For instance, the use of BRAF inhibitors in patients with BRAF-mutated melanoma and ALK inhibitors in patients with ALK-rearranged lung cancer (6) showed remarkably high response rates, even in the phase I setting.…”
Section: Discussionmentioning
confidence: 99%